Top Management Team Members' Decision Influence and Cooperative Behaviour: An Empirical Study in the Information Technology Industry. (4th March 2013) - Buyl, Tine; Boone, Christophe; Hendriks, Walter
<x xml:space="preserve">Abstract</x> Organizational leadership is generally distributed between the chief executive officer (CEO) and the top management team (TMT) members. Building on this observation, we present an empirical investigation of the cues for CEOs to delegate decision‐making influence to particular TMT members. In the literature, explanations both based on expertise and driven by similarity are described. In this study, we reconcile both explanations by examining the moderating role of the TMT's level of 'cooperative behaviour' (collaboration and information exchange). We analyse when and in what circumstances TMT members' expertise and similarity to the CEO regarding his/her functional background and/or locus‐of‐control predict their decision‐making influence. We postulate that TMT cooperative behaviour will advance the effect of expertise on TMT members' decision influence but impede the effect of similarity to the CEO. Our hypotheses are tested on a data set of 135 TMT members from 32 Dutch and Belgian information technology firms. Overall, we find that our proposed research model is confirmed for technology‐oriented decisions. Furthermore, we draw exploratory conclusions about the effect of TMT cooperative behaviour on the systematic distribution of decision influence in TMTs.